Enhancement of anti-tumor immune responses induced by ligand-mediated biomimetic Texosomes. Issue 61 (10th June 2016) - Wang, Zhongyan; Chang, Shasha; Zhao, Xiuli; Chen, Dawei; Li, Kexin
Abstract : In order to overcome the immune tolerance and awake the tumor patients' self immune response, hTERT-HSP70 as a universal tumor antigen is specifically transferred to dendritic cells by DEC205McAb Texosomes as the carriers of a tumor vaccine. Abstract : In order to overcome the immune tolerance and awake the tumor patients' self immune response, hTERT-HSP70 as a universal tumor antigen is specifically transferred to dendritic cells by DEC205McAb Texosomes as the carriers of a tumor vaccine. The strength of the immune response and the underlying mechanisms of inhibiting tumor growth are investigated here. Our results indicate that enhanced tumor specific immune responses elicited by DEC205McAb Texosomes might be attributed to the fact that dendritic cells have a more obviously phagocytic capacity on DEC205McAb Texosomes, and thereby promote internalizing, processing and presenting of antigens as well as trigger strong tumor-specific cytotoxic T lymphocyte reaction in lymph nodes, which consequently inhibit the tumor growth and prolong the survival period. In conclusion, tumor antigen loaded ligand-mediated biomimetic Texosomes targeting dendritic cells can overcome tumor immuno-suppression and enhance the anti-tumor immune response.